Effect of Rhododendron myrtifolium Schott & Kotschy Leaf Extracts on HCl-Induced Hemolysis in Human Erythrocytes - Prokopiv, Andriy; Tkachenko, Halyna; Honcharenko, Vitaliy; Kurhaluk, Natalia; Nachychko, Viktor; Sosnovsky, Yevhen; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Many species of the genus Rhododendron L. contain a large number of chemical compounds that possessed the antioxidant properties. Rhododendron myrtifolium Schott & Kotschy possesses cytotoxic, antibacterial, and antiviral effects, while its biochemical features and bioactive potentials remain unexplored. In the current study, the in vitro hemolytic activity of R. myrtifolium Schott & Kotschy extract in three different doses on human erythrocytes was evaluated. The total hemolysis (%) was obtained using 0.1M HCl compared to the phosphate saline buffer as a control sample. Therefore, the aim of the current study was to assess possible antioxidant and anti-hemolytic effects of extract derived from R. myrtifolium leaves using oxidative stress biomarker [2-thiobarbituric acid reactive substances (TBARS) as biomarker of lipid peroxidation] and HCl-induced hemolysis assay on human erythrocytes’ model after incubation with plant extracts in three doses (5.0, 2.5, and 1.25 mg/mL). Our results revealed that the treatment of human erythrocytes by extract derived from R. myrtifolium leaves in different doses (1.25, 2.5, 5.0 mg/mL) caused the statistically significant increase of TBARS level. The highest value of TBARS level was observed after the treatment of human erythrocytes by extract derived from R. myrtifolium leaves in 5.0 mg/mL. At this dose, protuberances and ruffled edges on erythrocytes were also noted. On the other hand, R. myrtifolium extract at 1.25 mg/mL caused the highest percent of hemolyzed erythrocytes and decrease hemolysis duration. This study demonstrated, that among the leaf extract of R. myrtifolium, the dose of 5 mg/mL exhibited the highest level of lipid peroxidation biomarker and morphological changes in the human erythrocytes. In addition, the study also demonstrated that R. myrtifolium leaf extract at dose 1.25 mg/mL possessed hemolytic effect in vitro compared to other doses studied. Therefore, further investigation of it's in vitro and in vivo activity is warranted.